Бюджетно-податкове стимулювання розвитку аграрного сектору України - Трусова, Наталя Вікторівна; Радченко, Наталія Геннадіївна; Шутько, Т. І.; Trusova, Natalia; Radchenko, Nataliia (Київ : ТОВ "ДКС Центр", 2021)
UA: У статті проведено дослідження сучасних тенденцій розвитку аграрної галузі України у період пандемії, результати якого свідчать про ефективне ведення підприємницької діяльності в аграрному секторі, але визначені й негативні результати та тенденції, які слід враховувати в майбутньому під час формування політики державного регулювання аграрного сектору. Проведений аналіз системи оподаткування свідчить про те, що суб'єктів господарювання аграрної сфери можна позиціонувати як активних платників податків, які мають достатньо високий потенціал для розвитку. Не менш важливим інструментом стимулювання аграрного сектору поряд з пільговим оподаткуванням є програми державної підтримки. В останні роки показники державної підтримки мають позитивну динаміку, але у порівнянні з іншими країнами світу, це не найкращі результати. Про низький загальний обсяг державної підтримки сільського господарства в Україні свідчать також результати досліджень, що проводить Організація економічного співробітництва та розвитку. EN: At the present stage of development of the world in the postMpandemic period, the support of agricultural producers becomes especially important. The agricultural sector has been and remains the basis for ensuring food security of the state and its economic development. The results of the study indicate the effective conduct of business in the agricultural sector, but also identified negative results and trends that must be taken into account in the future when formulating policies for state regulation of the agricultural sector. Budget and tax regulation has been the main direction of state regulation of the agar industry for several years in a row. The analysis of the taxation system shows that agricultural entities can be positioned as active taxpayers who have a high enough potential for development. The tax regulation tools applied by the government to the agricultural sector are effective. In our opinion, it is necessary to pay attention to such a category of agricultural producers as households. Today, the regulatory framework leaves such farms out of the legal field: they do not pay taxes, and on the other hand can not count on state support programs and appropriate social protection. No less important tool to stimulate the development of the agricultural sector along with preferential taxation are state support programs. We observe positive dynamics in terms of changes in government support, but compared to other countries, these are not the best results. The low total amount of state support for agriculture in Ukraine is also evidenced by the results of research conducted by the Organization for Economic Cooperation and Development. To increase the effectiveness of state support, in our opinion, it is necessary to: develop methodological approaches to assessing the effectiveness of the use of public funds; give preference to those businesses that demonstrate high productivity and efficiency; to create a stable system of state support programs for a period of 3M5 years, so that agricultural enterprises have the opportunity to plan their activities, taking into account the funds of state programs; increase the percentage of government spending on areas such as research, development and infrastructure for the development of the agar sector in the future; encourage cooperation in the acquisition and transfer of knowledge between public and private actors — at the national, regional and international levels.
Budget and tax incentives to agricultural sector development in Ukraine
Keywords: аграрний сектор; система оподаткування; податкові пільги; державна підтримка; бюджетноподаткове стимулювання; the agrarian sector; the system of taxation; tax payments; state sales; budgetary and tax incentives